Magnesium induced vascular relaxation and role of Calcium-dependent K+ Channels - Upadhyay-Dhungel, K; Kim, CJ; Dhungel, A (Janaki Medical College Journal of Medical Science, 2013)
Background and objectives: Magnesium is established as a neuro-protective agent and now also known as a vasodilator. It has been known for treating vasospasm following subarachnoid hemorrhage. However, its action mechanism in cerebral vascular relaxation is not clear. Potassium channels play a pivotal role in the relaxation of smooth muscle cells. To investigate their role in magnesium-induced relaxation of basilar smooth muscle cells, we examined the effect of magnesium on potassium channels using the patch clamp technique on cells from rabbit basilar artery. Material and Methods: Fresh smooth muscle cells were isolated from the basilar artery by enzyme treatment. Whole cell current recording was done using patch-clamp technique. Appropriate bath solution was used to have potassium current. The effect of Magnesium was observed and to identify the potassium (K+) channel involved in the magnesium-induced currents, different potassium channel blockers were used. Results: Magnesium increased the step pulse-induced outward K+ currents by more than fortyfive percent over control level (p<0.01). The outward K+ current was decreased significantly by application of tetraethylammonium, a non-specific K+ channel blocker, and by iberiotoxin, a largeconductance Ca2+-activated K+ (BKCa) channel blocker, but was not inhibited by glibenclamide an ATP-sensitive K+ (KATP) channel blocker. Magnesium failed to increase the outward K+ currents in the presence of IBX. Conclusion: These results demonstrate that calcium dependent pottassium (BKCa) channels has role in magnesium induced vascular relaxation in rabbit basilar smooth muscle cells and needs to be worked out for human. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7880 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):9-13